Pathogenesis and evolution of carpal instability: imaging and topography - De Filippo, M.; Sudberry, J.J.; Lombardo, et al., E. (Acta Biomedica Atenei Parmensis, 2006)
Carpal instability is a biomechanical alteration with a multiple pathogenesis which, if not identified and treated in time, leads to gradual articular collapse.Traumatism is known to be one of the main causes of carpal instability, while deposits of microcrystals caused by metabolic (chondrocalcinosis and gout) and congenital (ulna minus variance) diseases are less frequently involved in the pathogenesis. In forms secondary to traumatism, the trauma causes ligamentous injuries that lead to misalignments of the joint surfaces, or badly healed fractures with consequent articular incongruency. In both situations, an alteration of carpal kinematics is generated and, if normal carpal biomechanics are not restored, this alteration leads, over the course of time, to degenerative alterations of the cartilage, followed by chondral erosions and to the exposure of the bone.We present the etiology, topography and consequences of carpal instability, discussing the diagnostic procedure, which always begins with a conventional X-ray examination, followed by a CT and/or an MRI with an intra-articular injection of contrast medium as the gold standard for a correct evaluation. Our aim is to present and compare the different patterns of carpal instability observed in our Radiology Institute with those found in literature.